KEKUATAN DAN ARAH KEMAMPUAN METAKOGNISI, KECERDASAN VERBAL, DAN KECERDASAN INTERPERSONAL HUBUNGANNYA DENGAN HASIL BELAJAR BIOLOGI SISWA KELAS XI IPA SMA NEGERI 3 SUKOHARJO - Sholihah, Isnaini Maratus; Karyanto, Puguh; Sugiharto, Bowo (Pendidikan Biologi, 2012)
ABSTRACT ? This research is aimed to know the strenght and direction between: 1) metakognitif achievement and cognitive learning achievement of biological lesson of XI IPA student?s grade of SMA Negeri 3 Sukoharjo in academic year of 2011/2012, 2) Verbal intellegences and cognitive learning achievement of biological lesson of XI IPA student?s  grade of SMA Negeri 3 Sukoharjo in academic year of 2011/2012, 3) Interpersonal intelligences and  cognitive learning achievement of biological lesson of XI IPA student?s grade of SMA Negeri 3 Sukoharjo in academic year of 2011/2012. It is a kuntitatif correlational research. The population was taken all of students XI IPA grade of SMA Negeri 3 Sukoharjo in academic year of 2011/2012. The sample was taken using simple random sampling technique. Test technique was used to uncover student?s verbal  intellegences, documentation  technique was used  to uncover student?s cognitive learning achievement, while metakognition achievement and interpersonal intellegences was measured by using questionnaire. The obtained data was analysed using multiple linier regression analysis with SPSS 16. The result showed that (1) there is corellation between metakognition achievement and cognitive learning achievement of biological lesson of XI IPA student?s grade of SMA Negeri 3 Sukoharjo  in academic year of 2011/2012, with  the  regression coefficient is  0,238, the  relative  contribution  is 42,4% and the  effective contribution is 19,6%,  2) there is corellation between verbal intellegences and cognitive learning achievement of biological lesson of XI  IPA student?s grade of SMA Negeri 3 Sukoharjo in academic year of 2011/2012, with the  regression coefficient is 0,154, the relative  contribution  is 32% and the  effective  contribution is  14,8%,  3) there is corellation between interpersonal intellegences with cognitive learning achievement  of biological  lesson of XI IPA student?s grade of SMA Negeri 3 Sukoharjo in academic year of 2011/2012, with the  regression coefficient is 0,175, the relative contribution is 25,6% and the effective contribution is 11,8%. The three aforementioned corellation are considered as significant and positive valuable. They have 46,2% contribution to learning achievement of biological lesson. Each of independent variable that is metakognitif achievement, verbal intellegences and interpersonal intellegences has contribution to dependent variable, that is learning achievement of biological lesson. Student achievement at biological lesson as much as 53,8% is affected by other factor. Keywords:  metakognitif awareness, verbal intellegences, interpersonal intellegences, cognitive learning achievment of biological lesson